News. (Christian Century, 1999)
Presents news briefs on Christianity in the United States as of August 1999. Details on Episcopal Church's approval to full communion of the Evangelical Lutheran Church; Information on Kansas Board of Education's adoption of standards for teaching biology particulary the theory of evolution in public schools; Resignation of Archbishop Butch Spyridon as head of Greek Orthodox Archdiocese of America; Information on Boy Scouts of America's move to ban homosexuals in the association.